Perceived Social Influences on Women's Decisions to use Medications not Studied in Pregnancy. A Qualitative Ethical Analysis of Preexposure Prophylaxis Implementation Research in Kenya. (July 2021) - Ngure, Kenneth; Trinidad, Susan B.; Beima-Sofie, Kristin; Kinuthia, John; Matemo, Daniel; Kimemia, Grace; Njoroge, Anne; Achiro, Lillian; Pintye, Jillian; Mugo, Nelly R.; Bukusi, Elizabeth A.; Baeten, Jared M.; et al.
Implementation research ethics can be particularly challenging when pregnant women have been excluded from earlier clinical stages of research given greater uncertainty about safety and efficacy in pregnancy. The evaluation of human immunodeficiency virus (HIV) preexposure prophylaxis (PrEP) during pregnancy offered an opportunity to understand important ethical considerations and social influences shaping women's decisions to participate in the evaluation of PrEP and investigational drugs during pregnancy. We conducted interviews with women ( n = 51), focus groups with male partners (five focus group discussions [FGDs]), interviews with health providers ( n = 45), four FGDs with pregnant/postpartum adolescents and four FGDs with young women. Data were analyzed using thematic content analysis, including ethical aspects of the data. Our study reveals that women navigate a complex network of social influences, expectations, support, and gender roles, not only with male partners, but also with clinicians, family, and friends when making decisions about PrEP or other drugs that lack complete safety data during pregnancy.